Draft genome sequences of four Enterococcus faecium strains isolated from Argentine cheese - Martino, Gabriela Paula (2016)
We report the draft genome sequences of four Enterococcus faecium strains isolated from Argentine regional cheeses. These strains were selected based on their technological properties, i.e., their ability to produce aroma compounds (diacetyl, acetoin, and 2,3-butanediol) from citrate. The goal of our study is to provide further genetic evidence for the rational selection of enterococci strains based on their pheno- and genotype in order to be used in cheese production.